2013
DOI: 10.1166/jnn.2013.8091
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl Dextran-Cyclodextrin Conjugate as the Carrier of Doxorubicin

Abstract: The carboxymethyl dextran-y-cyclodextrin (CMD-yCD) conjugate was prepared as the carrier for the delivery of the poorly water-soluble anticancer drug, doxorubicin (DOX). The conjugate could form self-assembled nanoparticles (315 nm in diameter) in an aqueous solution, which might be due to the hydrogen bonding among yCD molecules in the conjugate. DOX was effectively encapsulated into CMD-yCD nanoparticles (CMD-NPs) by the emulsion method. In particular, regardless of the feed amount of DOX, its loading effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…During the synthesis procedure, degree of substitution (DS), defined as the number of LCAs per 100 CMD sugar residues, was controlled by varying the molar feed ratio of LCA to the carboxyl group in CMD. DS was calculated based on the integration ratio of the proton peak appearing from the methyl group of LCA at 0.70 ppm (18‐CH 3 ) and that from the carboxymethylene proton of CMD at 4.02 ppm . As expected, the DS of LCA increased as the feed ratio of LCA increased ( Table 1 ).…”
Section: Resultsmentioning
confidence: 58%
“…During the synthesis procedure, degree of substitution (DS), defined as the number of LCAs per 100 CMD sugar residues, was controlled by varying the molar feed ratio of LCA to the carboxyl group in CMD. DS was calculated based on the integration ratio of the proton peak appearing from the methyl group of LCA at 0.70 ppm (18‐CH 3 ) and that from the carboxymethylene proton of CMD at 4.02 ppm . As expected, the DS of LCA increased as the feed ratio of LCA increased ( Table 1 ).…”
Section: Resultsmentioning
confidence: 58%
“…High aqueous solubility and the ability to encapsulate hydrophobic moieties within their cavity through the formation of inclusion complexes enable cyclodextrins to enhance the solubility, stability, and bioavailability of hydrophobic small-molecule drugs. 319 320 Davis et al reported a cyclodextrin polymer-based nanoparticle delivery system for the systemic administration of siRNA to patients with solid tumors. 321 RNA interference was used to reduce the expression of M2-subunit of ribonucleotide reductase (RRM2).…”
Section: Cyclodextrin Nanoparticlesmentioning
confidence: 99%
“…Abbasi et al prepared â-cyclodextrin-helenalin complexes and showed that â-cyclodextrin-helenalin complexes inhibited the growth of the T47D breast cancer cell line. 324 Cyclodextrin could also be used to deliver the poorly water-soluble anticancer drug, doxorubicin. 325 …”
Section: Cyclodextrin Nanoparticlesmentioning
confidence: 99%
“…Hydrophilic PUs have several strengths, including maintenance of a moist environment, high absorbency for exudates and high moisture permeability. In addition to the synthetic polymers, natural biopolymers including hyaluronic acid, chitosan, and dextran derivatives have been extensively investigated in biomedical applications mainly because of their biocompatibility, non-immunogenicity, biodegradability and cell-adhesion properties [3,[29][30][31][32][33][34]. Among the variety of natural polysaccharides, chitosan is a positively charged linear polysaccharide composed of glucosamine and N-acetyl glucosamine derivatives, has been widely used as a wound dressing material [30].…”
Section: Introductionmentioning
confidence: 99%